Kecemasan dalam Menjelang Persalinan Ditinjau Dari Paritas, Usia dan Tingkat Pendidikan - Heriani, Heriani (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2016)
This study aims to determine the correlation of parity, age and education level with anxiety in during labor. This research is an analytic survey with cross sectional approach. A questionnaire was used as an instrument to collecting research data. The population in this study amounted to 45 people using accidental sampling technique. Statistical analysis using chi square at variable parity, age and education level of respondents' anxiety during labor in each obtained p value = 0.008, p value = 0.002, p value = 0.011. The role of health workers is very important in reducing anxiety in pregnant women in order to complications arising can be reduced so as to reduce maternal and infant mortality in Indonesia.Keywords: maternal anxiety, parity, age and education.